Impact of outdoor residual spraying on the biting rate of malaria vectors: A pilot study in four villages in Kayin state, Myanmar - Chaumeau, V; Kajeechiwa, L; Kulabkeeree, T; Vishwakarma, RK; Wasisakun, P; Hsel, SN; Oo, K; Dah, T; Sawasdichai, S; Trakoolchengkaew, M; Phanaphadungtham, M; Inta, A; et al. (Public Library of Science, 2020)
Outdoor and early mosquito biters challenge the efficacy of bed-nets and indoor residual spraying on the Thailand-Myanmar border. Outdoor residual spraying is proposed for the control of exophilic mosquito species. The objective of this study was to assess the impact of outdoor residual spraying on the biting rate of malaria vectors in Kayin state, Myanmar. Outdoor residual spraying using lambda-cyhalothrin was carried out in two villages in December 2016 (beginning of the dry season) and two villages were used as a control. Malaria mosquitoes were captured at baseline and monthly for four months after the intervention using human-landing catch and cow-baited trap collection methods. The impact of outdoor residual spraying on human-biting rate was estimated with propensity score adjusted generalized linear mixed-effect regressions. At baseline, mean indoor and outdoor human-biting rate estimates ranged between 2.12 and 29.16 bites /person /night, and between 0.20 and 1.72 bites /person /night in the intervention and control villages respectively. Using model output, we estimated that human-biting rate was reduced by 91% (95%CI = 88–96, P <0.0001) immediately after outdoor residual spraying. Human-biting rate remained low in all sprayed villages for 3 months after the intervention. Malaria vector populations rose at month 4 in the intervention villages but not in the controls. This coincided with the expected end of insecticide mist residual effects, thereby suggesting that residual effects are important determinants of intervention outcome. We conclude that outdoor residual spraying with a capsule suspension of lambda-cyhalothrin rapidly reduced the biting rate malaria vectors in this area where pyrethroid resistance has been documented.